Studi Literatur: Urgensi Efektivitas Peran Audit Internal dalam Upaya Pendeteksian dan Pencegahan Fraud Pada Perbankan - Afandi Afandi; Masculine Muhammad Muqorobin; Kartika Pradana Suryatimur (International Forum of Researchers and Lecturers, 2024)
This study aims to determine the urgency of the effectiveness of the role of internal audit as an effort to detect and prevent fraud in banking in Indonesia. This research was also conducted to determine the stages of implementing internal audit effectively with the aim of minimizing or as a form of fraud prevention and knowing things that can increase the effectiveness of internal audit. The writing method used is literature review both from books and journals related to the topic of discussion. The data source used is secondary data that is analyzed which is developed to explain the research topic. Based on the results of the research analysis, there are several stages carried out by internal audit to detect and prevent fraud in banking. In addition, internal audits can pay attention to several things that are crucial in improving banking effectiveness. The existence of a high level of effectiveness can create an independent internal audit department in banking, so that it can make a milestone of the company's strength by having expert, professional, and high-integrity resources.